The review of leading indicators of the stock market activity in Poland - Bogusława GARDZIEJEWSKA (Communications of International Proceedings, 2025)
This article presents a comprehensive review of the literature on leading indicators of stock market activity in Poland, aimed at identifying the most effective forecasting tools for market trends and economic cycles. The analysis includes publications from the Scopus and Web of Science databases, resulting in a collection of 63 articles, 11 of which directly address the Polish market. The studies are classified into four main groups: market indicators, banking sector indices, macroeconomic variables, and synthetic measures of financial stress and systemic risk. The review highlights the evolution of research approaches: from simple macroeconomic indicators used in the 1990s, through advanced econometric models and stress indices introduced after the 2008 global financial crisis, to sectoral analyses during the COVID-19 pandemic. The results confirm the high predictive value of stock market indices (including the WIG), the role of banking sector indicators in early warning systems, and the need to integrate macroeconomic data with risk analysis based on network models. This synthesis provides a structured source of knowledge for both researchers and market practitioners, and indicates directions for further research and development of economic situation monitoring systems.
Keywords: leading indicators; stock market; Poland